Examination of 5G NR, LTE, and NB-IoT Radio Interfaces and Their Vulnerabilities to Interference - Piotr Rajchowski (Journal of Telecommunications and Information Technology)
Modern cellular wireless communication systems of the fourth (4G) and fifth generation (5G) face a problem of various types of interference or intentional jamming. Consequently, a degradation of the services provided and an incorrect network operation may occur. In this paper, configuration of the networks' physical layer is investigated, with the said investigation preceded by the measurement of parameters of commercial networks operating in two different environments, to assess their vulnerabilities to interference or intentional jamming. Finally, a method for analyzing the radio signal received with the use of 5G New Radio (NR), Long Term Evolution (LTE), and Narrowband Internet of Things (NB-IoT) radio interfaces is proposed, to detect and mitigate the negative impact of unwanted signals. Software-based implementation of the proposed method allows one to detect and mitigate co-channel interference, intentional jamming and maintain compatibility of user equipment (UE) with the 3rd Generation Partnership Project (3GPP) standard, as it does not affect operations performed, for instance, at the time and frequency synchronization or channel parameter estimation phases.